UMPSA launches ASEAN Exploration Expedition Programme - MUHAMMAD ZUFLI, ZUHARI (UMPSA, 2023)
PEKAN, 27 October 2023 – The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dato’ Ts. Dr. Yuserrie Zainuddin, who is also the Deputy Chairman of the UMP Foundation, presented the UMPSA flag and plaque to three Project Managers of the ASEAN Exploration Expedition Programme at the Banquet Hall, UMPSA Pekan.